3D Galactic extinction modelling. Issue Volume 9:Issue S298(2013) (6th January 2014) - Hanson, Richard J.; Bailer-Jones, Coryn A. L.
Abstract: Using multi-band photometry we train a forward model to emulate the colour-change due to temperature and extinction for stars. We simultaneously solve for the astrophysical parameters (APs) extinction A 0, temperature T eff and distance modulus μ r in a Bayesian framework for individual stars. We introduce an HRD prior to account for previous knowledge about the distribution of stars in the temperature- absolute magnitude plane (see also Bailer-Jones 2011). This allows us to infer distance information. We obtain the full three dimensional PDFs of all the stars in a field, allowing us to determine extinction-distance profiles for a given line of sight.